1970
DOI: 10.3329/jom.v10i2.2820
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Epidemiology of Stroke :A Study of 100 Cases

Abstract: The stroke patients comprise a large number of hospital admissions and stroke is one of leading cause of significant mortality and morbidity. This prospective observational study was carried out among 100 hospitalized stroke patients admitted into different medicine units of Chittagong Medical College Hospital (CMCH), with a view to study clinical presentation and epidemiology of stroke. Data, collected in prescribed protocol, were analyzed in simple statistical percentage and cases were selected irrespective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
38
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 4 publications
19
38
1
3
Order By: Relevance
“…Following stroke, nystagmus is reported in an average of 11% (range 4 to 48%) in three studies (n=438) [35,62,65]. In most prospective and retrospective studies reporting nystagmus, the specific types of nystagmus are not reported.…”
Section: Nystagmusmentioning
confidence: 99%
“…Following stroke, nystagmus is reported in an average of 11% (range 4 to 48%) in three studies (n=438) [35,62,65]. In most prospective and retrospective studies reporting nystagmus, the specific types of nystagmus are not reported.…”
Section: Nystagmusmentioning
confidence: 99%
“…This study reveals mean age of stroke as 58.36±14.80 years and frequency of stroke in male and female patients are 68% and 32% respectively. A study from Chittagong Medical College, Bangladesh demonstrates that middle class group has the highest risk of ischemic strokes and housewives are most commonly affected group 19 . Our study also demonstrates higher incidence of stroke in middle socioeconomic class (34%) and the commonest in housewives occupation (32%).…”
Section: Discussionmentioning
confidence: 99%
“…Menurut penelitian oleh Siddique dkk. 17 di Dhaka 53,75% pasien strok iskemi berusia 51-60 tahun dengan jumlah pasien laki-laki lebih banyak. Penelitian oleh Picelli dkk.…”
Section: Pembahasanunclassified